Financial Analysis as a Key Component of the Business Valuation - Yanko Hristozov (International Business and Accounting Research Journal, 2021)
Corporate managers are responsible for acquiring material and financial resources and using them to create value for the company's investors. Value is created when a company realizes a return on its investment above the cost of capital. Managers formulate business strategies to achieve this goal and implement them through business activities. The business activity of the company is influenced by its economic environment and own business strategy. The economic environment includes the company's industry, its markets for incoming and outgoing products and the regulations under which the company operates. The analysis of the financial condition is used to assess the readiness of the company to take the financial risk and the ability to repay its debts. It is also used by creditors to assess the creditworthiness of the company. Methodology: The purpose of this article is to consider the possibilities of financial analysis in the valuation of enterprises. The main task of the article will be to highlight the key indicators, part of the financial analysis, which are applicable in the evaluation of operating enterprises. The thesis that is defended is related to the need to apply financial analysis in the evaluation of existing enterprises and for this purpose it is possible to derive an appropriate methodology based on the most appropriate financial indicators.